(BO)2‐Doped Tetrathia[7]helicene: A Configurationally Stable Blue Emitter. Issue 5 (20th December 2022) - Menduti, Luigi; Baldoli, Clara; Manetto, Simone; Bolte, Michael; Lerner, Hans‐Wolfram; Longhi, Giovanna; Villani, Claudio; Licandro, Emanuela; Wagner, Matthias
Abstract: Helicenes combine two central themes in chemistry: extended π‐conjugation and chirality. Hetero‐atom doping preserves both characteristics and allows modulation of the electronic structure of a helicene. Herein, we report the (BO)2 ‐doped tetrathia[7]helicene 1, which was prepared from 2‐methoxy‐3, 3′‐bithiophene in four steps. 1 is formally derived by substituting two (Mes)B−O moieties in place of (H)C=C(H) fragments in two benzene rings of the parent tetrathia[7]helicene. X‐ray crystallography revealed a dihedral angle of 50.26(9)° between the two terminal thiophene rings. The ( P )‐/( M )‐1 enantiomers were separated by chiral HPLC and are configurationally stable at room temperature. The experimentally determined enantiomerization barrier of 27.4±0.1 kcal mol −1 is lower than that of tetrathia[7]helicene (39.4±0.1 kcal mol −1 ). The circular dichroism spectra of ( P )‐ and ( M )‐1 show a perfect mirror‐image relationship. 1 is a blue emitter ( λ em =411 nm) with a photoluminescence quantum efficiency of Φ PL =6 % ( cf . tetrathia[7]helicene: λ em ≈405 nm, Φ PL =5 %). Abstract : A BO‐doped thiahelicene has been synthesized by a four‐step procedure and its optoelectronic and chiroptical properties investigated. The incorporation of two B−O bonds into the tetrathia[7]helicene framework has resulted in a configurationally stable (Δ G enant ≠ =27.4±0.1 kcal mol −1 ) blue emitter ( Φ PL =6 %).